2022
DOI: 10.21009/jpensil.v11i2.26578
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Characteristics of the Choice of Transportation Modes in the City of West Jakarta During the Covid-19 Pandemic

Abstract: The Covid-19 pandemic that has hit the world in recent years has changed the habit of life of many people, with no exception to the West Jakarta City Administration citizen.. Various citizen activities started to adjust to the current living circumstances. This study was conducted to determine the relationship between the characteristics of mode selection and the usage of types of transportation modes in the Administrative City of West Jakarta during the Covid-19 Pandemic. This research data was obtained throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to Basuki et al (2017) generally, there are several transport modeling categories available for macro and micro planning. According to Reizsky Reynaldy et al (2022), based on previous research, it also identified factors that influence the choice of modes of public Terminal Guntur Melati studied based on Ministry of Communications Regulation No. 40 Of 2015 concerning Service Standards for the Implementation of Road Passenger Transport Terminals.…”
Section: Introductionmentioning
confidence: 99%
“…According to Basuki et al (2017) generally, there are several transport modeling categories available for macro and micro planning. According to Reizsky Reynaldy et al (2022), based on previous research, it also identified factors that influence the choice of modes of public Terminal Guntur Melati studied based on Ministry of Communications Regulation No. 40 Of 2015 concerning Service Standards for the Implementation of Road Passenger Transport Terminals.…”
Section: Introductionmentioning
confidence: 99%